Broadening Diversity in Medicine: Outcomes of the Drexel Pathway to Medical School Postbaccalaureate Medical Science Program. - Cestone, Christina; Russo, Donna; Berardi-Demo, Linda; Weber, Valerie; White, Michael; Shumsky, Jed; Baird, Doug; Walker, Loretta; Núñez, Ana (Journal of Best Practices in Health Professions Diversity: Education, Research & Policy)
Many academic health centers implement premedical post-baccalaureate programs (PBPs) to enhance the recruitment and retention of underrepresented groups in medicine. The goal is to create a more diverse physician workforce, mirroring the patient population being served. The purpose of this 5-year retrospective study was to examine the longitudinal performance of students participating in the Drexel Pathway to Medical School (DPMS) PBP, as compared to a randomly selected peer group of medical students who did not participate. Many DPMS students entered medical school with lower GPA and MCATs, yet performed on par with the comparison group. DPMS students took slightly longer to graduate versus control students, however, this difference was not statistically significant. Means for licensing exams differed, but were comparable to their peers. We conclude that establishing metrics for evaluation and monitoring student performance in a PBP was essential to achieving the desired outcomes for DPMS students-careers in medicine.